2018
DOI: 10.1088/1741-2552/aadee9
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop stimulation of the pelvic nerve for optimal micturition

Abstract: This novel approach may be applied to an implantable device for treating underactive bladder (<60% VE), especially in cases where under- or over-stimulation of the nerve is a concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…We may use "dystrophic neuritic nest" or "dystrophic neuritic plexus" to describe the format or profile of the curl-up neurites and coiled neurites. For control of the micturition process, the several routes relate a closed loop system [49,50]. N-d neurons involve the autonomic input fibers and preganglionic output.…”
Section: Discussionmentioning
confidence: 99%
“…We may use "dystrophic neuritic nest" or "dystrophic neuritic plexus" to describe the format or profile of the curl-up neurites and coiled neurites. For control of the micturition process, the several routes relate a closed loop system [49,50]. N-d neurons involve the autonomic input fibers and preganglionic output.…”
Section: Discussionmentioning
confidence: 99%
“…While on-demand pelvic nerve stimulation at prestipulated timepoints can help to empty the bladder, available on-line information about the fullness of the bladder could enable more flexible on-demand scheduling, and more effective delivery of stimulation under a closed-loop neuromodulation scheme 21 . Other than implanting devices that detect bladder size or pressure changes directly 32 , previous studies have shown that it was possible to correlate intravesical pressures with in vivo neural recordings obtained from the pelvic nerve [33][34][35] , pudendal nerve 36 , dorsal root ganglion 37 , and lumbar/sacral roots [38][39][40][41] in various species (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A graphic user interface on a laptop was used to set stimulation parameters, and initiate stimulation on-demand via a wireless link to the external device which then sent data and power to the stimulator. Based on results from a prior study on electrical stimulation of the pelvic nerve 21 , we decided to employ a multi-train stimulation approach to void the bladder. At each bihourly stimulation timepoint (i.e.…”
Section: Electrical Stimulation Of Pelvic Nerve In Awake Sci Ratsmentioning
confidence: 99%
“…All the aforementioned methods are based on the open-loop control manner. A closed-loop control has been proposed for control of bladder function while the intravesical pressure (IVP) has been employed as the feedback information 32,33 . Two pressure thresholds were defined to trigger the low-frequency continuous PN stimulation and intermittent high-frequency pudendal afferent stimulation.…”
Section: A General Framework For Automatic Closed-loop Control Of Blamentioning
confidence: 99%